Human IL-17 and TNF-α Additively or Synergistically Regulate the Expression of Proinflammatory Genes, Coagulation-Related Genes, and Tight Junction Genes in Porcine Aortic Endothelial Cells - Li, Weilong; Chen, Pengfei; Zhao, Yanli; Cao, Mengtao; Hu, Wenjun; Pan, Litao; Sun, Huimin; Huang, Dongsheng; Wu, Hanxi; Song, Zhuoheng; Zhong, Huanli; Mou, Lisha; et al. (Frontiers in Immunology, 2022)
Immune rejection is the major limitation for porcine xenograft survival in primate recipients. Proinflammatory cytokines play important roles in immune rejection and have been found to mediate pathological effects in various clinical and experimental transplantation trials. IL-17 and TNF-α play critical pathological roles in immune disorders, such as psoriasis and rheumatoid arthritis. However, the pathological roles of human IL-17 (hIL-17) and human TNF-α (hTNF-α) in xenotransplantation remain unclear. Here, we found that hIL-17 and hTNF-α additively or synergistically regulate the expression of 697 genes in porcine aortic endothelial cells (PAECs). Overall, 415 genes were found to be synergistically regulated, while 282 genes were found to be additively regulated. Among these, 315 genes were upregulated and 382 genes were downregulated in PAECs. Furthermore, we found that hIL-17 and hTNF-α additively or synergistically induced the expression of various proinflammatory cytokines and chemokines (e.g., IL1α, IL6, and CXCL8) and decreased the expression of certain anti-inflammatory genes (e.g., IL10). Moreover, hIL-17 plus hTNF-α increased the expression of IL1R1 and IL6ST, receptors for IL1 and IL6, respectively, and decreased anti-inflammatory gene receptor expression (IL10R). hIL-17 and hTNF-α synergistically or additively induced CXCL8 and CCL2 expression and consequently promoted primary human neutrophil and human leukemia monocytic (THP-1) cell migration, respectively. In addition, hIL-17 and hTNF-α induced pro-coagulation gene (SERPINB2 and F3) expression and decreased anti-coagulation gene (TFPI, THBS1, and THBD) expression. Additionally, hIL-17 and hTNF-α synergistically decreased Occludin expression and consequently promoted human antibody-mediated complement-dependent cytotoxicity (CDC). Interestingly, hTNF-α increased swine leukocyte antigen (SLA) class I expression; however, hIL-17 decreased TNF-α-mediated SLA-I upregulation. We concluded that hIL-17 and hTNF-α likely promote the inflammatory response, coagulation cascade and xenoantibody-mediated cell injury. Thus, blockade of hIL-17 and hTNF-α together might be beneficial for xenograft survival in recipients.